Pengaruh Suku Bunga Dan Inflasi Terhadap Profitabilitas (ROA) Pada Bank Umum Syariah - Ila Komalasari; Gusganda Suria Manda (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to analyze the effect of interest rate risk and inflation risk on the profitability of Return On Assets (ROA) at Islamic Commercial Banks registered with Bank Indonesia for the 2015-2019 period. The variables used in this study are the BI interest rate and the inflation rate. In this study, the research method used is descriptive quantitative method and the data processing uses multiple linear regression methods. The population in this study were Sharia Commercial Banks registered with Bank Indonesia, and the sampling technique used was simple random sampling technique, in which a sample of 6 Islamic Commercial Banks was obtained for the 2015-2019 period. The results obtained are (1) Partial interest rates have no effect on ROA profitability. (2) The inflation rate partially has no effect on ROA profitability. (3) Simultaneous interest rates and inflation rates have no effect on ROA profitability.